2020
DOI: 10.1007/s12111-020-09499-y
|View full text |Cite
|
Sign up to set email alerts
|

“What’s Happened to the People?” Gentrification and Racial Segregation in Brooklyn

Abstract: This article explores the relationship between gentrification and racial segregation in Brooklyn, New York with an emphasis on Black Brooklyn. With more than 2.6 million residents, if Brooklyn was a city, it would be the fourth largest in the USA. Brooklyn is the home of approximately 788,000 Blacks with almost 692,000 of them living in an area that historian Harold X. Connolly has called Black Brooklyn. In recent decades, large portions of Brooklyn, including parts of Black Brooklyn have been gentrifying with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…It also primes areas in which EB-5 projects are sited to go the way of the rest of the hypergentrified city, remade for the benefit of whiter and more affluent developers, investors, residents, and consumers, and largely inaccessible to everyone else. This study is exploratory in nature, building on research that documents the trajectory of gentrification and racial transition (Chronopoulos, 2016(Chronopoulos, , 2020Freeman, 2006;Hyra, 2017;Lees, 2016;Sutton, 2020), while underappreciating how the growing influence of foreign real estate investment intersects with historic and contemporary racial and spatial inequality. Since the EB-5 program is a prominent policy tool for attracting wealthy immigrant investors, and since New York City ranks highly among sites of transnational real estate investment and as a global symbol of gentrification and racial transition, it is appropriate to use the two in a single case study that illuminates connections between neoliberal governance, foreign capital, and gentrification's racialized human toll.…”
Section: Introductionmentioning
confidence: 99%
“…It also primes areas in which EB-5 projects are sited to go the way of the rest of the hypergentrified city, remade for the benefit of whiter and more affluent developers, investors, residents, and consumers, and largely inaccessible to everyone else. This study is exploratory in nature, building on research that documents the trajectory of gentrification and racial transition (Chronopoulos, 2016(Chronopoulos, , 2020Freeman, 2006;Hyra, 2017;Lees, 2016;Sutton, 2020), while underappreciating how the growing influence of foreign real estate investment intersects with historic and contemporary racial and spatial inequality. Since the EB-5 program is a prominent policy tool for attracting wealthy immigrant investors, and since New York City ranks highly among sites of transnational real estate investment and as a global symbol of gentrification and racial transition, it is appropriate to use the two in a single case study that illuminates connections between neoliberal governance, foreign capital, and gentrification's racialized human toll.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has demonstrated persistent racial segregation and racialised removal of communities as a result of housing policy in the United States (Chronopoulos, 2020; Kirkland, 2008; Sutton, 2020) and in urban spaces globally (Danewid, 2020). Our research responds to the prompt to understand gentrification as a state-led project (Lees, 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Crown Heights, Brooklyn, was, according a 1985 New York Times article, "regarded for years as a dangerous ghetto", yet in a pattern followed by many other American cities, it has now become "the poster child for gentrification" (Hoffawer 2022). With rising rents, predatory landlords who allow buildings to fall into disrepair, and an influx of wealthy new arrivals, existing social housing residents (like those pictured in Renault's photographs, Figures 6-8) are sometimes evicted, find themselves having to live in untenable conditions, or are simply forced to move on (Chronopoulos 2020). It is hard to quantify just how many residents have been displaced; data show that some immigrant communities who moved to Crown Heights from the West Indies and Trinidad have gone back, while others have moved to other U.S. cities such as Boston, Philadelphia, or Atlanta (Yee 2015).…”
Section: Jules Renaultmentioning
confidence: 99%